ZnO / PES mixed matrix ultrafiltration membrane and polyaniline-ZnO / PES mixed matrix nanofiltration membrane as well as preparation method and application of ZnO / PES mixed matrix ultrafiltration membrane and polyaniline-ZnO / PES mixed matrix nanofiltration membrane

Through the combination of ZnO/PES mixed matrix ultrafiltration membrane and polyaniline-ZnO/PES mixed matrix nanofiltration membrane, the high investment in the combustion alkali recovery process and the inability to recover lignin are solved, and the efficient recovery of alkali in black liquid and the high-value utilization of lignin are achieved. It has the advantages of simple operation, low energy consumption and environmentally friendly.

CN120479222APending Publication Date: 2025-08-15SOUTH CHINA UNIV OF TECH
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510838910.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-23
Publication Date
2025-08-15

AI Technical Summary

Technical Problem

When treating paper black liquor, the combustion alkali recovery process has a high investment and large area, and cannot recover lignin. The treatment of non-wood raw material black liquor is expensive. Traditional biological treatment technology faces the problems of high toxicity and difficulty in degradation.

Method used

The ZnO/PES mixed matrix ultrafiltration membrane was combined with the polyaniline-ZnO/PES mixed matrix nanofiltration membrane, and the alkali and lignin in the black liquid were separated by pressure differential filtration, and the membrane materials were prepared by non-solvent-induced phase conversion method and sol-gel method to improve the hydrophilicity and anti-pollution properties of the membrane.

Benefits of technology

It realizes efficient alkali recovery and high-value utilization of lignin, simple process, small investment, small land, low energy consumption, and environmentally friendly, which solves the shortcomings of traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120479222A_ABST
    Figure CN120479222A_ABST
Patent Text Reader

Abstract

The invention discloses a ZnO / PES mixed matrix ultrafiltration membrane and a polyaniline-ZnO / PES mixed matrix nanofiltration membrane as well as a preparation method and an application of the ZnO / PES mixed matrix ultrafiltration membrane and the polyaniline-ZnO / PES mixed matrix nanofiltration membrane. PES is used as an organic polymer, PEG1500 is used as a pore-foaming agent, ZnO is used as a nano filler, and the ZnO / PES composite ultrafiltration membrane is prepared through a non-solvent induced phase inversion method. The preparation method comprises the following steps: synthesizing a polyaniline coated ZnO nano composite material, blending zinc nitrate hexahydrate in ammonia water with a polyaniline solution to form a nano composite structure, and preparing the polyaniline-ZnO / PES mixed matrix nanofiltration membrane by taking the synthesized nano composite particles as a filler. According to the mixed matrix membrane technology, alkali and lignin in the black liquor can be directly recovered, compared with alkali recovery through a combustion method, the mixed matrix membrane technology has the advantages of being easy to operate, not complex in process, low in investment cost, small in occupied area, low in energy consumption, good in environmental compatibility and the like, and meanwhile subsequent high-valued comprehensive utilization can be conducted on lignin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of wastewater treatment, and particularly relates to a ZnO / PES mixed matrix ultrafiltration membrane and a polyaniline-ZnO / PES mixed matrix nanofiltration membrane as well as a preparation method and application thereof. Background Art

[0002] The papermaking and pulping process primarily includes raw material preparation, pulping, bleaching, and chemical recovery. The wastewater generated during the cooking process is the most concentrated and darkest wastewater in the entire pulping process, collectively referred to as black liquor. Black liquor contains large amounts of lignin, hemicellulose, pigments, sugars, residual alkali, and other leachables. It exhibits high color, odor, high alkalinity, and a high organic content, making it a difficult environmental pollutant to control.

[0003] Currently, there are many studies on the treatment of papermaking black liquor, and some treatment technologies are relatively mature. However, due to the high concentration of black liquor pollutants, large investment, high operating costs, and difficulty in process construction, the application of current treatment technologies is still relatively difficult. The main methods used by the papermaking industry at home and abroad to treat papermaking black liquor are to recover and treat the residual chemicals and fiber raw materials in papermaking black liquor and to make comprehensive use of them. These methods include combustion alkali recovery, acid precipitation, black liquor gasification, biological treatment, and membrane separation. The combustion alkali recovery process can not only recycle the alkali in the black liquor, but also provide energy for the factory. Therefore, it is most widely used in pulp and paper mills. However, due to the high investment cost of this process, resources such as lignin in the black liquor cannot be recovered for comprehensive utilization. Therefore, finding a new method that can replace the black liquor alkali recovery process has gradually become a consensus among the majority of papermaking researchers.

[0004] The combustion-based alkali recovery process is currently the most common black liquor treatment method used in pulp and paper mills. The alkali recovery process primarily involves three steps: evaporation, combustion, and causticization. First, the black liquor extracted from the cooking liquor is concentrated in a multi-effect evaporator to a solids content of 60% to 75%. Once the black liquor reaches a suitable combustion concentration, it is sprayed into a combustion furnace. Organic matter such as lignin in the black liquor burns in the furnace, releasing heat energy that is used to generate steam for power generation or heating. The inorganic sodium salts in the concentrated black liquor melt at high temperatures to form a molten product. This molten product dissolves in water to form green liquor, which primarily contains Na2CO3 and Na2S. Lime (CaO) is added to the green liquor to convert the Na2CO3 into NaOH, which becomes the alkali liquor used for pulping. This byproduct, white mud, primarily composed of CaCO3, is also produced. After washing and calcination, the lime is recovered and reused in the causticization process, forming a closed-loop system. The alkali recovery process not only reduces pollutant emissions in the pulp and paper industry but also recovers over 90% of the alkali. Furthermore, the heat generated by the combustion of concentrated black liquor can meet 50% to 70% of the factory's energy needs, reducing pulp and paper production costs. However, this process is primarily suitable for wood-based pulping black liquor. Non-wood raw materials (such as bamboo, grass, and reed pulp) contain high silicon content, which interferes with the evaporation and combustion of the black liquor and requires pre-desiliconization treatment, which is very expensive.

[0005] The acid precipitation method is a traditional process for treating papermaking black liquor by separating lignin from black liquor. During the cooking process, due to the action of caustic soda, the lignin macromolecules in the black liquor are degraded by cooking and become lignin sodium salt, existing in the form of R-ONa. The basic principle of the acid precipitation method is electrophilic substitution reaction, that is, under acidic conditions, hydrogen ions replace Na in alkaline lignin. + , thereby destroying the soluble alkaline lignin colloid and forming an insoluble precipitate, namely acid precipitation lignin precipitation. Although acid precipitation technology can extract lignin from black liquor, impurities will be introduced during the acidification process of black liquor, resulting in a decrease in product quality. At the same time, the alkali is completely reacted, making it impossible to recycle the alkali in the black liquor.

[0006] Black liquor gasification refers to the process of introducing an appropriate amount of air into a high-temperature gasifier to cause a gasification reaction between the black liquor and the air, generating fuel gases such as CO, CH4, and H2. The black liquor gasification mechanism is highly complex and can be divided into four stages: drying, thermal decomposition, combustion, and coke gasification. The advantage of black liquor gasification is that it can convert black liquor into synthesis gas, which can then be synthesized into liquid fuels such as methanol and dimethyl ether, which can be used as a substitute for fossil fuels. The black liquor gasification process also allows for the recovery of sodium carbonate and its conversion into sodium hydroxide solution. Therefore, black liquor gasification technology is considered one of the most promising alternatives to combustion.

[0007] The application of biological treatment technology in papermaking black liquor is to degrade or transform organic matter in black liquor through the metabolic activities of microorganisms. It has the advantages of being environmentally friendly, low cost and having high resource utilization potential. However, due to the high toxicity, high salinity, high alkalinity and difficult-to-degrade characteristics of black liquor, traditional biological treatment technology faces many challenges.

[0008] Membrane separation is a technology that allows components to selectively pass through the membrane and separate by applying a pressure difference on both sides of the membrane. Compared with traditional heat-based evaporation and distillation technologies, it has the advantages of low energy consumption, short operation time, good safety and environmental compatibility, and is therefore widely used in separation and purification. According to the filter pore size and molecular weight cut-off size, it can be divided into microfiltration (MF), ultrafiltration (UF), nanofiltration (NF) and reverse osmosis (RO). Membrane separation technology provides a new way for the efficient treatment and resource utilization of black liquor, but it still needs to solve the problems of membrane fouling, high salt tolerance and cost through material innovation, process optimization and system integration. With the expansion of the market for high-value utilization of lignin, the economic efficiency of membrane separation technology will be further improved, promoting the transformation of the papermaking industry to a green circular economy.

[0009] Mixed matrix membranes (MMMs) are advanced membrane materials that combine an organic polymer matrix with inorganic fillers. The organic polymer matrix of MMMs is the core component, serving as the continuous phase of the MMM, encapsulating and dispersing the inorganic fillers. Its primary functions include providing structural support, providing overall membrane stability, and ensuring mechanical strength (such as tensile and compressive properties); determining the membrane formation process (such as solution casting, phase inversion, interfacial polymerization, and electrospinning); and providing pathways for material transport, participating in molecular transport through the free volume or inherent pores between polymer segments. Commonly used organic polymer matrices for MMMs include polyethersulfone (PES), polysulfone (PSF), polyimide (PI), polyvinylidene fluoride (PVDF), and polydimethylsiloxane (PDMS). Applications of MMMs in water treatment primarily include wastewater treatment, seawater desalination, and oil-water separation.

[0010] At present, the main method for treating black liquor in pulp and paper mills is to recover alkali by combustion. The biggest disadvantages of this method are: (1) it is necessary to build a power plant to recover the heat energy from the combustion of black liquor, which requires a large investment and requires a large area; (2) it can only recover alkali, not lignin, and it is impossible to make high-value comprehensive utilization of lignin.

[0011] The ZnO / PES mixed matrix ultrafiltration membrane prepared by the present invention is combined with the polyaniline-ZnO / PES mixed matrix nanofiltration membrane to utilize the pressure difference for filtering black liquor, thereby separating the alkali and lignin in the black liquor, realizing the recovery of the alkali and the subsequent high-value comprehensive utilization of the lignin. The process is simpler than the black liquor combustion method, and the operation is convenient and the investment is small. Summary of the Invention

[0012] The present invention provides a ZnO / PES mixed matrix ultrafiltration membrane and a polyaniline-ZnO / PES mixed matrix nanofiltration membrane, as well as preparation methods and applications. In the present invention, a ZnO / PES composite ultrafiltration membrane is first prepared by a non-solvent-induced phase inversion method using PES as an organic polymer, PEG1500 as a porogen, ZnO as a nanofiller, and DMAc (N,N-dimethylacetamide) as a solvent. The prepared ZnO / PES composite ultrafiltration membrane is primarily used for deep pretreatment of papermaking black liquor. Secondly, a polyaniline-coated ZnO nanocomposite material is synthesized by a sol-gel method. Zinc nitrate hexahydrate is used as a ZnO precursor and blended with a polyaniline solution in ammonia water to form a nanocomposite structure. The synthesized nanocomposite particles are then used as fillers to prepare a polyaniline (PANI)-ZnO / PES mixed matrix nanofiltration membrane. The two membranes are combined to recover alkali from the black liquor while intercepting lignin for subsequent high-value comprehensive utilization, providing a new approach for black liquor treatment and high-value utilization. The primary membrane used was a polyethersulfone (PES) mixed-matrix membrane. Hydrophilic fillers were added to improve the hydrophilicity and anti-fouling properties of the PES. Using PES as the organic polymer matrix, ZnO and PANI-ZnO nanofillers were added to improve the membrane's physical properties, permeability, and selective separation capabilities. The resulting membranes were used for black liquor filtration, and the final alkali and lignin recoveries were measured.

[0013] The main technical contents are:

[0014] (1) Using nano-ZnO as filler, PES as polymer matrix, PEG as porogen, and DMAc as solvent, a ZnO / PES mixed matrix ultrafiltration membrane was prepared by a non-solvent induced phase inversion method. The viscosity of the casting solution was measured, the structure and physical properties of the membrane were characterized, the permeability, separation performance, and anti-fouling performance of the membrane were measured, the effect of ZnO content on the various properties of the membrane was analyzed, and the optimal ZnO addition amount was selected.

[0015] (2) Using zinc nitrate hexahydrate as a precursor, PANI-ZnO nanoparticles were synthesized and characterized by the sol-gel method. PANI-ZnO nanoparticles were used as fillers to increase the content of PES polymer matrix. PANI-ZnO / PES mixed matrix nanofiltration membranes were prepared by the non-solvent induced phase inversion method. The viscosity of the casting solution was also measured, and the structure and physical properties of the filter membrane were characterized. Its permeability, separation performance and anti-fouling performance were measured. The influence of PANI-ZnO content on the various properties of the filter membrane was analyzed, and the optimal PANI-ZnO addition amount was selected.

[0016] (3) The ultrafiltration membrane and nanofiltration membrane with the best performance were used for black liquor filtration. Before filtration, the black liquor was pre-treated by filtration with a 0.45 μm filter membrane to remove suspended matter. The pre-treated filtrate was then filtered by ultrafiltration and nanofiltration (0.1 MPa negative pressure). After the filtration, the effective alkali and lignin contents of the black liquor before filtration and the permeate after filtration at each stage were measured respectively, and finally the effective alkali recovery rate and lignin retention rate were calculated.

[0017] The invention discloses a method for preparing a ZnO / PES mixed matrix ultrafiltration membrane for alkali recovery of papermaking black liquor. The method adopts polyethersulfone (PES) as an organic polymer, polyethylene glycol (PEG1500) as a porogen, ZnO as a nanofiller, and N,N-dimethylacetamide (DMAc) as a solvent to prepare the ZnO / PES composite ultrafiltration membrane through a non-solvent induced phase inversion method.

[0018] The specific steps are:

[0019] (1) Dry PES, PEG and nano-ZnO in a vacuum drying oven at 35-40°C for 10-12 h;

[0020] (2) dispersing nano ZnO in a DMAc solvent in an ultrasonic bath, then adding PES and PEG to the mixed solution under stirring, stirring at room temperature until completely dissolved, ultrasonically treating the prepared solution for 20 to 30 minutes after stirring to avoid the formation of nano particle aggregates, and finally keeping it at room temperature for 4 to 5 hours to remove bubbles, to obtain a casting solution; the content of nano ZnO in the casting solution is 0.2% to 1.0%; the content of PES in the casting solution is 15% to 16%; and the content of PEG in the casting solution is 3% to 5%;

[0021] (3) Cast the casting liquid on a clean and flat glass plate, and use a 200 μm scraping rod to uniformly apply the casting liquid on the surface of the glass plate. After keeping it in the air for 25 to 30 seconds, place the glass plate in a deionized water coagulation bath; after the composite film is completely detached, transfer it to a new deionized water bath and soak it for 24 to 30 hours to remove the residual solvent.

[0022] A method for preparing a polyaniline-ZnO / PES mixed matrix nanofiltration membrane for alkali recovery of papermaking black liquor comprises the following steps: synthesizing a polyaniline-coated ZnO nanocomposite material by a sol-gel method; using zinc nitrate hexahydrate as a precursor of ZnO and blending it with a polyaniline solution in ammonia water to form a nanocomposite structure; and then using the synthesized nanocomposite particles as fillers to prepare a polyaniline (PANI)-ZnO / PES mixed matrix nanofiltration membrane.

[0023] The specific steps are:

[0024] (1) Synthesis of polyaniline (PANI): 1-2 mL of aniline was added to 25 mL of 1 M hydrochloric acid in an ice-water bath, and an aqueous ammonium persulfate solution was added dropwise under constant stirring. The mixture was reacted in an ice-water bath for 3-4 h. After the reaction, the mixture was filtered with filter paper, and the product was washed with deionized water until the filtrate was almost colorless. The product was then dried in a vacuum drying oven at 50-60°C. The temperature of the ice-water bath was 0-5°C to obtain polyaniline.

[0025] (2) PANI-ZnO nanoparticles were synthesized by the following steps: 0.4-0.6 g of zinc nitrate hexahydrate was dissolved in 50 mL of deionized water, and then 2-3 mL of ammonia water and 18-22 mL of polyaniline solution were added under magnetic stirring, and the mixture was kept at 70-75° C. for 10-12 h; the mixture was filtered with filter paper, washed with deionized water, and finally dried in a vacuum drying oven at 50-60° C. and ground to obtain PANI-ZnO nanoparticles; the concentration of polyaniline in the polyaniline solution was 0.02-0.03 g / mL;

[0026] (3) PANI-ZnO / PES mixed matrix membrane was prepared using polyethersulfone PES as polymer, N,N-dimethylacetamide DMAc as solvent, polyethylene glycol PEG1500 as porogen, and PANI-ZnO particles as filler: PANI-ZnO nanoparticles obtained in step (2) were dispersed in DMAc solvent in an ultrasonic bath, PES and PEG1500 were added to the mixed solution in a ratio of 9:1 to 11:1 under stirring, and stirred at room temperature until completely dissolved. After stirring, the prepared solution was ultrasonically treated to avoid the formation of aggregates and kept at room temperature for 4 to 5 hours to degas. The method comprises the steps of: bubbling the PANI-ZnO nanoparticles to obtain a casting solution; casting the casting solution onto a clean and flat glass plate, uniformly coating the casting solution on the surface of the glass plate with a 200-μm scraping rod, maintaining the casting solution in air for 30 to 35 seconds, placing the glass plate in a deionized water coagulation bath, and transferring the composite film to a new deionized water bath and soaking the bath for 24 to 30 hours to remove residual solvent after the composite film is completely detached, thereby obtaining a PANI-ZnO / PES mixed matrix membrane; the concentration of the PANI-ZnO nanoparticles in the DMAc solvent is 0.1 to 0.5 wt %; and the amount of the PANI-ZnO nanoparticles added to the casting solution is 0.1 to 0.5 wt %.

[0027] In the above method, in step (1), the preparation method of the ammonium persulfate aqueous solution is: dissolving 2-2.5g of ammonium persulfate oxidant in 25mL of deionized water under stirring.

[0028] Compared with the prior art, the advantages of the present invention are:

[0029] The combustion-based alkali recovery process is currently the most commonly used black liquor treatment method in pulp and paper mills. However, it has high investment and operating costs, is difficult to construct, occupies a large area, cannot recover lignin, and cannot achieve high-value comprehensive utilization of lignin. At the same time, this process is only applicable to pulping black liquor made from wood. Non-wood raw materials (bamboo, grass, reed pulp, etc.) have a high silicon content, which will interfere with the evaporation and combustion of the black liquor, making it impossible to use the combustion method for alkali recovery.

[0030] The mixed matrix membrane technology of the present invention can directly recover alkali and lignin in black liquor. Compared with the combustion method for alkali recovery, it has the advantages of simple operation, uncomplicated process, low investment cost, small footprint, low energy consumption, and good environmental compatibility. At the same time, it can carry out subsequent high-value comprehensive utilization of lignin. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the cross-sectional SEM image of the ZnO / PES mixed matrix ultrafiltration membrane;

[0032] Figure 2 This is the UV absorption spectrum of ZnO / PES mixed matrix ultrafiltration membrane;

[0033] Figure 3 This is the tensile stress / strain curve of the ZnO / PES mixed matrix ultrafiltration membrane;

[0034] Figure 4 The flux and retention rate of lignin solution filtered by ZnO / PES mixed matrix ultrafiltration membrane;

[0035] Figure 5 This is the cross-sectional SEM image of the PANI-ZnO / PES mixed matrix nanofiltration membrane;

[0036] Figure 6 This is the UV absorption spectrum of PANI-ZnO / PES mixed matrix nanofiltration membrane;

[0037] Figure 7 This is the tensile stress / strain curve of PANI-ZnO / PES mixed matrix nanofiltration membrane;

[0038] Figure 8 The flux and retention rate of lignin solution filtered by PANI-ZnO / PES mixed matrix nanofiltration membrane. DETAILED DESCRIPTION

[0039] The following description, combined with specific illustrations, illustrates the technical solutions for a thorough understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein. Similar generalizations and implementations made by persons of ordinary skill in the art without inventive effort are also within the scope of protection of the present invention.

[0040] Example 1

[0041] Preparation of ZnO / PES mixed matrix ultrafiltration membrane

[0042] The materials and reagents used in this example are shown in Table 1 below:

[0043] Table 1 Reagents used in the preparation and performance study of ZnO / PES composite membranes

[0044]

[0045] Mixed matrix ultrafiltration membranes were prepared using non-solvent induced phase inversion technology (NIPS): PES was used as polymer, DMAc was used as solvent, PEG1500 was used as porogen, and nano-zinc oxide was added at concentrations of 0.2%, 0.4%, 0.6%, 0.8% and 1.0% by mass, respectively. The effects of these additions on the membrane structure and performance were analyzed.

[0046] PES, PEG, and nano-zinc oxide were dried in a vacuum oven at 40°C for 12 hours. A casting solution was then prepared according to the composition listed in Table 2-3. First, nano-ZnO was dispersed in DMAc solvent in an ultrasonic bath. PES and PEG were then added to the mixed solution under magnetic stirring and stirred at room temperature for 8 hours until completely dissolved. After stirring, the solution was ultrasonically treated for 30 minutes to prevent the formation of nanoparticle aggregates. Finally, the solution was maintained at room temperature for 5 hours to remove air bubbles, resulting in a casting solution.

[0047] The casting solution was poured onto a clean, flat glass plate. A 200μm doctor blade was used to uniformly apply the solution to the glass surface. After holding the solution in air for 30 seconds, the glass plate was placed in a deionized water coagulation bath. After the composite film was completely removed, it was transferred to a fresh deionized water bath and immersed for 24 hours to remove any residual solvent. The composition of the casting solution is shown in Table 2.

[0048] Table 2 Composition of each component of the casting solution

[0049]

[0050] Scanning electron microscopy (SEM) was used to analyze the cross-sectional morphology and microstructure of the ZnO / PES ultrafiltration membrane. Figure 1 As shown in Figure 2, the membrane has a typical asymmetric structure, with a dense porous surface layer and a loose porous or sponge-like sublayer, and the surface layer and the sublayer are connected by finger-like straight pores. The ZnO / PES ultrafiltration membrane was characterized by ultraviolet-visible absorption spectroscopy (UV-vis). Figure 2 As shown in the figure, with the increase of the amount of nano ZnO added, its characteristic peak in the 320-380nm range increases, indicating that the nano ZnO is successfully loaded in the filter membrane. The ZnO / PES ultrafiltration membrane was subjected to a tensile test using a material testing machine. Figure 3As shown in Figure 2, the maximum tensile stress of the membrane reaches 4.2-4.56 MPa, and the presence of nano ZnO increases the maximum tensile stress of the membrane. Figure 4 As shown, when the ZnO content is 0.4%, the ZnO / PES ultrafiltration membrane has the highest flux and best permeability, while when the ZnO content is 0.8%, the ultrafiltration membrane has the highest lignin retention rate. Therefore, in this example, these two ultrafiltration membranes were used to filter black liquor to test the ZnO / PES ultrafiltration membrane's lignin retention rate and effective alkali recovery rate. The research showed that the ultrafiltration membrane had a black liquor lignin retention rate of approximately 20%, a hemicellulose retention rate of between 50% and 60%, and an effective alkali recovery rate of over 90%.

[0051] Example 2

[0052] Preparation of polyaniline-ZnO / PES mixed matrix nanofiltration membrane

[0053] Experimental materials and reagents

[0054] The materials and reagents used in this experiment are shown in Table 3 below:

[0055] Table 3 Reagents used in the preparation and performance study of PANI-ZnO / PES composite membranes

[0056]

[0057] Other materials and reagents are shown in Table 1.

[0058] This example uses a sol-gel method to synthesize PANI-ZnO nanoparticles. The synthesis process consists of two distinct parts. In the first part, the synthesis steps of polyaniline are as follows: First, 2.25g of ammonium persulfate oxidant is dissolved in deionized water under magnetic stirring. Then, 1mL of aniline is added to 25mL of 1M hydrochloric acid in an ice-water bath. The ammonium persulfate aqueous solution is added dropwise with constant stirring. The reaction is carried out in an ice-water bath (0-5°C) for 3 hours. After the reaction is completed, the product is filtered with filter paper, washed with deionized water until the filtrate is nearly colorless, and then dried in a 50°C vacuum drying oven. In the second part, PANI-ZnO nanoparticles are synthesized by the following steps: First, 0.5g of zinc nitrate hexahydrate is dissolved in 50mL of deionized water. Then, 2mL of ammonia water is added under magnetic stirring. After 30 minutes, the polyaniline solution containing approximately 0.5g of polyaniline is added to the above mixed solution and maintained at 70°C for 12 hours. The product was filtered with filter paper, washed with deionized water, and finally dried in a vacuum drying oven at 50°C and ground to obtain the final product.

[0059] A PANI-ZnO / PES mixed matrix membrane was prepared using polyethersulfone (PES) as the polymer, N,N-dimethylacetamide (DMAc) as the solvent, polyethylene glycol (PEG1500) as the porogen, and PANI-ZnO particles as the filler. PANI-ZnO particles (0-0.5 wt%) were dispersed in DMAc (78 wt%) in an ultrasonic bath. PES (20 wt%) and PEG (2 wt%) were added to the mixed solution under magnetic stirring and stirred at room temperature for 8 hours until completely dissolved. After stirring, the solution was ultrasonically treated for 30 minutes to prevent aggregate formation and then held at room temperature for 5 hours to remove air bubbles, resulting in a casting solution. The casting solution was then cast onto a clean, flat glass plate and uniformly coated onto the surface using a 200 μm doctor blade. After holding the solution in air for 30 seconds, the glass plate was placed in a deionized water coagulation bath. After the composite membrane was completely detached, it was transferred to a new deionized water bath and soaked for 24 h to remove the residual solvent, obtaining a PANI-ZnO / PES mixed matrix membrane.

[0060] Table 4 Composition of each component of the casting solution

[0061]

[0062] PANI-ZnO nanoparticles were successfully synthesized by the sol-gel method, and then a PES-based mixed matrix membrane containing PANI-ZnO was successfully prepared by a non-solvent-induced phase inversion method. The cross-sectional morphology and microstructure of the PANI-ZnO / PES nanofiltration membrane were analyzed by scanning electron microscopy (SEM). Figure 5 As shown in Figure 2, the nanofiltration membrane also has a typical asymmetric structure, with a dense porous surface layer and a loose porous sublayer, which are connected by finger-like straight pores. The PANI-ZnO / PES nanofiltration membrane was characterized by ultraviolet-visible absorption spectroscopy (UV-vis). Figure 6 As shown in the figure, with the increase of the amount of nano-PANI-ZnO added, the characteristic peaks of ZnO in the 320-380nm range and PANI in the 550-700nm range both increased, indicating that the PANI-ZnO particles were successfully loaded in the filter membrane. The ZnO / PES ultrafiltration membrane was subjected to a tensile test using a material testing machine. Figure 7 As shown in Figure 2, the maximum tensile stress of the membrane reaches 6.31-7.16 MPa, and the presence of PANI-ZnO particles increases the maximum tensile stress of the membrane. The PANI-ZnO / PES nanofiltration membrane was tested for lignin solution filtration. Figure 8As shown, when the PANI-ZnO content is 0.4%, the ZnO / PES ultrafiltration membrane has the highest flux and best permeability, while when the ZnO content is 0.2%, the ultrafiltration membrane has the highest lignin retention rate. Therefore, in this example, these two ultrafiltration membranes were used to filter black liquor to test the PANI-ZnO / PES nanofiltration membrane's lignin retention rate and effective alkali recovery rate. The research showed that the nanofiltration membrane had a retention rate of approximately 55% for ultrafiltration and black liquor lignin, a retention rate of between 20% and 30% for hemicellulose, and an effective alkali recovery rate of approximately 85%.

[0063] Example 3

[0064] Analysis of total lignin, hemicellulose and alkali recovery rates of black liquor after ultrafiltration and nanofiltration:

[0065] (1) During the filtration of black liquor using 0.4% ZnO / PES ultrafiltration membrane and 0.4% PANI-ZnO nanofiltration membrane at room temperature, the changes in the lignin, hemicellulose and effective alkali contents of the black liquor are shown in Table 5 below:

[0066] Table 5 Changes of black liquor lignin, hemicellulose and effective alkali content during filtration

[0067]

[0068] As can be seen from Table 5, after treatment with 0.4% ZnO / PES ultrafiltration and 0.4% PANI-ZnO / PES nanofiltration, the lignin and hemicellulose retention rates of the black liquor finally reached 63.26% and 65.81%, and the recovery rate of effective alkali reached 81.23%.

[0069] (2) During the filtration of black liquor using 0.4% ZnO / PES ultrafiltration membrane and 0.2% PANI-ZnO nanofiltration membrane at room temperature, the changes in the lignin, hemicellulose and effective alkali contents of the black liquor are shown in Table 6 below:

[0070] Table 6 Changes of black liquor lignin, hemicellulose and effective alkali content during filtration

[0071]

[0072] As can be seen from Table 6, after treatment with 0.4% ZnO / PES ultrafiltration and 0.2% PANI-ZnO / PES nanofiltration, the lignin and hemicellulose retention rates of the black liquor finally reached 66.8% and 68.1%, and the recovery rate of effective alkali reached 78.77%.

[0073] In summary, after the black liquor was filtered through the "ultrafiltration + nanofiltration" double membrane of the present invention, the filtration effects of 0.2% PANI-ZnO / PES and 0.4% PANI-ZnO / PES filter membranes were compared and analyzed, and it was concluded that the 0.4% PANI-ZnO / PES filter membrane had more advantages in black liquor nanofiltration. The lignin and hemicellulose retention rates of the black liquor finally reached 63.26% and 65.81%, and the recovery rate of effective alkali reached 81.23%.

Claims

1. A method for preparing a ZnO / PES mixed matrix ultrafiltration membrane for alkali recovery from papermaking black liquor, characterized in that: ZnO / PES composite ultrafiltration membrane was prepared by non-solvent induced phase inversion method using polyethersulfone (PES) as organic polymer, polyethylene glycol (PEG1500) as porogen, ZnO as nanofiller and N,N-dimethylacetamide (DMAc) as solvent.

2. The method for preparing a ZnO / PES mixed matrix ultrafiltration membrane for alkali recovery of papermaking black liquor according to claim 1, characterized in that: The specific steps are: (1) Dry PES, PEG and nano-ZnO in a vacuum drying oven at 35-40°C for 10-12 h; (2) dispersing nano ZnO in a DMAc solvent in an ultrasonic bath, then adding PES and PEG to the mixed solution under stirring, stirring at room temperature until completely dissolved, ultrasonically treating the prepared solution for 20 to 30 minutes after stirring to avoid the formation of nano particle aggregates, and finally keeping it at room temperature for 4 to 5 hours to remove bubbles, to obtain a casting solution; the content of nano ZnO in the casting solution is 0.2% to 1.0%; the content of PES in the casting solution is 15% to 16%; and the content of PEG in the casting solution is 3% to 5%; (3) Cast the casting liquid on a clean and flat glass plate, and use a 200 μm scraping rod to uniformly apply the casting liquid on the surface of the glass plate. After keeping it in the air for 25 to 30 seconds, place the glass plate in a deionized water coagulation bath; after the composite film is completely detached, transfer it to a new deionized water bath and soak it for 24 to 30 hours to remove the residual solvent.

3. A method for preparing a polyaniline-ZnO / PES mixed matrix nanofiltration membrane for alkali recovery from papermaking black liquor, characterized in that: Polyaniline-coated ZnO nanocomposites were synthesized by the sol-gel method. Zinc nitrate hexahydrate was used as a precursor of ZnO and mixed with polyaniline solution in ammonia water to form a nanocomposite structure. The synthesized nanocomposite particles were then used as fillers to prepare polyaniline (PANI)-ZnO / PES mixed matrix nanofiltration membranes.

4. The method for preparing a polyaniline-ZnO / PES mixed matrix nanofiltration membrane for alkali recovery of papermaking black liquor according to claim 3, characterized in that: The specific steps are: (1) Synthesis of polyaniline (PANI): 1-2 mL of aniline was added to hydrochloric acid in an ice-water bath, and an aqueous ammonium persulfate solution was added dropwise thereto under constant stirring. The mixture was reacted in an ice-water bath for 3-4 hours. After the reaction, the mixture was filtered with filter paper, and the product was washed with deionized water until the filtrate was almost colorless. The product was then dried in a vacuum drying oven at 50-60°C; the temperature of the ice-water bath was 0-5°C to obtain polyaniline. (2) PANI-ZnO nanoparticles were synthesized by the following steps: 0.4-0.6 g of zinc nitrate hexahydrate was dissolved in 50 mL of deionized water, and then 2-3 mL of ammonia water and 18-22 mL of polyaniline solution were added under magnetic stirring, and the mixture was kept at 70-75° C. for 10-12 h; the mixture was filtered with filter paper, washed with deionized water, and finally dried in a vacuum drying oven at 50-60° C. and ground to obtain PANI-ZnO nanoparticles; the concentration of polyaniline in the polyaniline solution was 0.02-0.03 g / mL; (3) PANI-ZnO / PES mixed matrix membrane was prepared using polyethersulfone PES as polymer, N,N-dimethylacetamide DMAc as solvent, polyethylene glycol PEG1500 as porogen, and PANI-ZnO particles as filler: PANI-ZnO nanoparticles obtained in step (2) were dispersed in DMAc solvent in an ultrasonic bath, PES and PEG1500 were added to the mixed solution in a ratio of 9:1 to 11:1 under stirring, and stirred at room temperature until completely dissolved. After stirring, the prepared solution was ultrasonically treated to avoid the formation of aggregates and kept at room temperature for 4 to 5 hours to degas. The method comprises the steps of: bubbling the PANI-ZnO nanoparticles to obtain a casting solution; casting the casting solution onto a clean and flat glass plate, uniformly coating the casting solution on the surface of the glass plate with a 200-μm scraping rod, maintaining the casting solution in air for 30 to 35 seconds, placing the glass plate in a deionized water coagulation bath, and transferring the composite film to a new deionized water bath and soaking the bath for 24 to 30 hours to remove residual solvent after the composite film is completely detached, thereby obtaining a PANI-ZnO / PES mixed matrix membrane; the concentration of the PANI-ZnO nanoparticles in the DMAc solvent is 0.1 to 0.5 wt %; and the amount of the PANI-ZnO nanoparticles added to the casting solution is 0.1 to 0.5 wt %.

5. The method for preparing a polyaniline-ZnO / PES mixed matrix nanofiltration membrane for alkali recovery of papermaking black liquor according to claim 4, characterized in that: In step (1), the preparation method of the ammonium persulfate aqueous solution is as follows: 2-2.5 g of ammonium persulfate oxidant is dissolved in 25 mL of deionized water under stirring.

6. The ZnO / PES mixed matrix ultrafiltration membrane prepared by the preparation method according to claim 1 or 2.

7. A polyaniline-ZnO / PES mixed matrix nanofiltration membrane prepared by the preparation method according to any one of claims 3 to 5.

8. Applying the ZnO / PES mixed matrix ultrafiltration membrane according to claim 6 and the polyaniline-ZnO / PES mixed matrix nanofiltration membrane according to claim 7 to alkali recovery of papermaking black liquor.

Citation Information

Cited By

  • Alkali-resistant film for paper pulp waste liquid treatment and preparation method of alkali-resistant film

    CN122252047A

  • Alkali-resistant film for pulp waste liquid treatment and preparation method thereof

    CN122252047B